Preliminary design on high-end workstation cooling system using loop heat pipes - Choi, Jeehoon; Jeong, Minjoong (Thermal science and engineering progress, 2020)
•Preliminary design is introduced to implement quick modeling on a loop heat pipe cooling system.•Design optimization based on a real coded genetic algorithm was devised to provide various configurations of design variables.•Multidimensional visualization tool was adapted to discern the most suitable design among solutions.•Prototype was constructed and tested to verify the proposed design process. This paper introduces a new approach for the preliminary design of high-end workstation cooling system using loop heat pipe. To demonstrate this approach, a multidimensional visualization environment tool with respect to design optimization based on a genetic algorithm was devised not only to provide various configurations of design variables but also to conduct quickly preliminary design from the viewpoint of commercially viable versions and manufacturing. The optimization utilizing a real coded genetic algorithm was implemented to appropriately determine the configuration design variables of loop heat pipe components associated with the pressure drop, subject to specified design constraints. Through the devised visualization environment, various configurations can be identified so that cooling system modelers can promptly select the optimal candidate at the preliminary design stage when the proposed design condition and configurations are needed for decision making. As a case study, we designed a workstation cooling system based on the loop heat pipe that enabled to transport heat of 200 W CPU toheat exchanger. The highest temperature was 50.7 °C, which is sufficiently low to run multi-core CPUs. The experimental results show that the preliminary design optimization based cooling prototype to be a solution for achieving superior thermal performance in high-end workstations.